Central H(2) histaminergic and alpha-2 adrenergic receptors involvement in crocetin-induced antinociception in orofacial formalin pain in rats - Erfanparast, Amir (Vet Res Forum, 2020)
Previous findings have shown that saffron (Crocus sativus L.) extract and its active constituents produce antinociceptive effects in the rat models of orofacial pain. In the present study, the central H(2) histaminergic and alpha-2 adrenergic receptors involvement in crocetin-induced antinociception in orofacial formalin pain in rats was evaluated. The guide cannula was implanted into the fourth ventricle in ketamine-xylazine anesthetized rats. Subcutaneous injection of a diluted formalin solution (1.50%; 50.00 µL) into a vibrissae pad was used as a model of orofacial pain. Face rubbing behavior durations were recorded at 3 min blocks for 45 min. Formalin produced a biphasic pain response (first phase: 0-3 min and second phase: 15-33 min). Intra-fourth ventricle injections of crocetin (5.00 and 10.00 μg μL(-1)) suppressed, whereas yohimbine (10.00 μg μL(-1)) and naloxone (10.00 μg μL(-1)) increased the intensity of both phases of pain. Crocetin-induced antinociception was not prevented by central pretreatment with naloxone. However, the antinociceptive effect of crocetin (5.00 μg μL(-1)) was inhibited by prior administration of famotidine (10.00 μg μL(-1)) and yohimbine (10.00 μg μL(-1)). Our study showed that injection of crocetin into the cerebral fourth ventricle attenuated formalin-induced orofacial pain in rats. Central H(2) histaminergic and alpha-2 adrenergic receptors, but not opioid receptors, might be involved in crocetin-induced antinociception.